Pericardial calcification: A case report of a three-dimensional disease. (2019) - Ohri, Raja; Salhiyyah, Kareem; Harding, Stephen; Ohri, Sunil
Highlights: Constrictive pericarditis is an important cause of diastolic heart failure. Pericardial calcification is present in less than 25% of all cases of CP. Chest X-ray is valuable detector of pericardial calcification, a surrogate of pericardial constriction. Pericardial calcification is a three-dimensional condition, and should be investigated by lateral CXR, CT scan and appropriate functional imaging. Abstract: Introduction: Constrictive pericarditis is an important cause of diastolic heart failure. The relationship between the presence and degree of pericardial calcification with constrictive pericarditis is variable, however this should be an early warning sign to initiate appropriate investigations. Presentation of case: A 64-year-old gentleman presented with dyspnoea and dizziness on exertion. Plain posterior-anterior chest X-ray showed mild to moderate pericardial calcification. He had an episode of atrial fibrillation which resolved spontaneously and thought to be the cause of his symptoms. Patient symptoms progressed. Further investigations including CT scan confirmed extensive constrictive pericarditis. He underwent a successful percardiectomy and full recovery. Discussion: Constrictive pericarditis can be the consequence of different conditions such as tuberculosis, radiation, idiopathic or many others. Pericardial calcification is present in less than 25% of all cases of constrictive pericarditis, and patient with it are prone to develop atrial fibrillation. The presence of pericardial calcification on plain chest radiograph is an important indicator for the possibility of pericardial dysfunction. Many cases of pericardial calcification are benign without any clinical significance; however three-dimensional imaging is required to determine the calcium load and aid in reaching appropriate diagnosis. Conclusion: Chest X-ray is valuable detector of pericardial calcification, a surrogate of pericardial constriction, but it is important to remember that pericardial calcification is a three-dimensional condition, and should be further investigated by lateral chest X-ray, CT scan and then appropriate functional imaging.